Water-based adhesive and method of manufacturing and application thereof

KR103012480B1Active Publication Date: 2026-09-01SHENZHEN YANYI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020247032465
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2022-12-21
Publication Date
2026-09-01
Estimated Expiration
2042-12-21

Smart Images

  • Figure 112024105879088-PCT00001
    Figure 112024105879088-PCT00001
  • Figure 112024105879088-PCT00002
    Figure 112024105879088-PCT00002
Patent Text Reader

Abstract

The present invention discloses an aqueous adhesive and a method for manufacturing and applications thereof, wherein the aqueous adhesive is a copolymer formed by a polymer metal salt and a polymerizable monomer; wherein the polymerizable monomer comprises a combination of an acrylate monomer and an olefin monomer, and the polymer metal salt is selected from any one or at least two combinations of a metal phosphate polymer, a metal carboxylate polymer, a metal sulfonate polymer, or a metal bissulfonylimide polymer. The present application, through the design of structural units such as the polymer metal salt and the polymerizable monomer and their mutual cooperation, enables the formed copolymer segment to include a specific repeating structural unit, thereby enabling the aqueous adhesive to have appropriate swelling characteristics, excellent adhesive performance and lithium-ion conductivity, and to possess excellent adhesive strength, adhesive stability and electrochemical properties, thereby significantly improving the cycle performance and scaling performance of a lithium-ion battery containing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The embodiments of the present application relate to the field of lithium-ion battery material technology, for example, aqueous adhesives and methods for manufacturing the same and applications. Background Technology

[0002] In recent years, the performance enhancement of lithium-ion batteries has faced significant challenges in meeting the demands of electrification equipment and devices, particularly the further development of the mobile phone and electric vehicle industries. Currently, the market has not only presented demands for higher energy density in lithium-ion batteries but is also making the need for fast charging capabilities increasingly important. Adhesives are one of the key components of battery electrodes and are used to connect active materials, conductive agents, and electrode current collectors to ensure overall connectivity between them. During the charge-discharge process, adhesives effectively maintain the structural integrity of the electrodes, ensuring that the electrode materials can repeatedly perform lithium insertion and extraction, and play a crucial role in maintaining cycle performance. Since adhesives have a significant impact on the electrical performance of the electrodes and batteries, high-performance lithium-ion batteries require high-performance adhesives to match.

[0003] Polyvinylidene fluoride (PVDF) is currently the most commonly used oil-based adhesive in lithium-ion batteries; while it possesses superior redox capabilities and stability, N - Methylpyrrolidone (NMP) must be used as a solvent to ensure good dispersion, but NMP has a high volatilization temperature and is expensive, as well as being detrimental to human health and posing a risk of environmental pollution; furthermore, since PVDF is prone to hydrolysis, ambient humidity must be strictly controlled during the electrode manufacturing process, which increases battery production costs and causes PVDF to swell in the electrolyte, affecting the reliability and safety of battery use.

[0004] Adopting water-based adhesives to replace oil-based adhesives such as PVDF in order to ensure that lithium battery production processes meet environmental requirements is one of the current development trends for battery electrodes. Currently, existing water-based adhesives include polyacrylic acid (PAA), sodium carboxymethylcellulose / styrene-butadiene rubber (CMC / SBR), sodium alginate, and chitosan. Among these, SBR-type adhesives are widely used in negative electrode systems because they require a small amount of addition in the system and have strong adhesion to the active material and current collector; however, the components of SBR adhesives have low polarity and poor affinity with highly polar electrolytes, and the kinetic performance of lithium-ion batteries manufactured using these adhesives is inferior, making it impossible to achieve satisfactory rapid charging performance. Furthermore, SBR is typically used in combination with the thickener CMC, but CMC has average adhesive performance and high brittleness, causing the electrode to crack easily during charging and discharging. CN109802139A discloses an aqueous adhesive and a battery, wherein the aqueous adhesive comprises an adhesive component and a thickening component, wherein the adhesive component comprises any one of styrene-butadiene rubber and polyacrylic acid, and the thickening component comprises one of cyclodextrin and chitosan; this aqueous adhesive can effectively reduce the shuttle effect of intermediate products, lower the risk of detachment, and improve the electrochemical performance of the battery; however, because polyacrylic acid has a higher vitrification transition temperature and is harder at room temperature, the electrodes may become rigid and brittle, PAA aqueous adhesives are prone to cracking during the coating process, defects such as streaks appear after cold pressing, and powder detachment occurs at the folded portions of the electrodes during the winding process, thereby limiting their widespread application in batteries. Furthermore, while natural polymer materials such as sodium alginate and chitosan show excellent performance as adhesives in terms of environmental protection and water solubility, they have many shortcomings in terms of electrochemical performance, mechanical performance, and adhesive performance, making it difficult to meet the application requirements of batteries.

[0005] Therefore, developing water-based adhesive materials that combine excellent adhesion, scaling, and cycle performance to meet the application requirements of high-performance battery electrodes and lithium-ion batteries is an urgent task that the industry must address.

[0006] The following is an overview of the subjects described in detail in this application. This overview is not intended to limit the scope of protection of the claims.

[0007] The embodiments of the present application provide an aqueous adhesive and a method for manufacturing the same and applications, and through the design of structural units such as polymer metal salts and polymerizable monomers, the aqueous adhesive is made to have excellent adhesive performance, lithium ion conductivity and appropriate swelling characteristics, which can be used in battery electrodes and lithium-ion batteries to significantly improve the cycle performance and scaling performance of the battery.

[0008] In a first aspect, embodiments of the present application provide an aqueous adhesive, said aqueous adhesive being a copolymer formed by a polymeric metal salt and a polymerizable monomer; said polymerizable monomer comprising a combination of an acrylate monomer and an olefin monomer; said polymeric metal salt being selected from any one or at least two combinations of a metal phosphate polymer, a metal carboxylate polymer, a metal sulfonate polymer, or a metal bissulfonylimide polymer.

[0009] The aqueous adhesive provided in this application is a copolymer formed by the reaction of a polymer metal salt and a polymerizable monomer, wherein the polymerizable monomer comprises a combination of acrylate-based monomers and olefin-based monomers having different solubility parameters, and through the design of structural units such as specific types of polymer metal salts and polymerizable monomers, the formed copolymer segments are configured to include specific repeating structural units to obtain a product having different solubility parameters and to ensure that the aqueous adhesive has appropriate swelling characteristics; at the same time, structural fragments of the polymer metal salt can improve the strength and metal salt content of the adhesive, thereby ensuring that the aqueous adhesive has excellent adhesive performance and lithium-ion conductivity. The aqueous adhesive provided in this application achieves an excellent balance effect between adhesive performance, lithium-ion conductivity, and swelling characteristics through the design of structural units within the copolymer, and possesses excellent adhesive strength, adhesive stability, and electrochemical performance, thereby significantly improving the cycle performance and scaling performance of battery electrodes and lithium-ion batteries containing the same.

[0010] Preferably, the polymer metal salt comprises any one or at least two combinations of polymer lithium salt, polymer sodium salt, polymer potassium salt, or polymer magnesium salt.

[0011] Preferably, the metal phosphate-based polymer is selected from any one or at least two combinations of metal polyphosphate, metal 2-methyl-2-acrylate-2-hydroxyethyl phosphate-based polymer, metal bis(2-(methacryloyloxy)ethyl)phosphate-based polymer, metal 2-methacryloyloxyethyl phosphate-based polymer, or metal vinyl phosphate-based polymer, and more preferably, it is any one or at least two combinations of lithium polyphosphate, lithium 2-methyl-2-acrylate-2-hydroxyethyl phosphate-based polymer, lithium bis(2-(methacryloyloxy)ethyl)phosphate-based polymer, lithium 2-methacryloyloxyethyl phosphate-based polymer, or lithium vinyl phosphate-based polymer.

[0012] Preferably, the metal carboxylate-based polymer is selected from any one or at least two combinations of metal methacrylate-based polymers, metal acrylate-based polymers, metal maleate-based polymers, metal itaconate-based polymers, metal trialyl citrate-based polymers, metal carboxymethylcellulose-based polymers, or metal alginate-based polymers, and more preferably, it is any one or at least two combinations of lithium methacrylate-based polymers, lithium acrylate-based polymers, lithium maleate-based polymers, lithium itaconate-based polymers, lithium trialyl citrate-based polymers, lithium carboxymethylcellulose-based polymers, or lithium alginate-based polymers.

[0013] Preferably, the metal sulfonate-based polymer is selected from any one or a combination of at least two of the following: a metal styrenesulfonate-based polymer, a metal vinylsulfonate-based polymer, a metal acrylsulfonate-based polymer, a metal methylallylsulfonate-based polymer, a metal 4-vinylbenzenesulfonate-based polymer, a metal allylvinylsulfonate-based polymer, a metal 3-sulfopropyl methacrylate-based polymer, a metal 2-sulfoethyl methacrylate-based polymer, a metal 2-acrylamido-2-methyl-1-propanesulfonate-based polymer, a metal acrylate-2-acrylamido-2-methylpropanesulfonate-based polymer, and a metal 3-allyloxy-2-hydroxy-1-propanesulfonate-based polymer; more preferably, a lithium styrenesulfonate-based polymer, a sodium styrenesulfonate-based polymer, a potassium styrenesulfonate-based polymer, a lithium vinylsulfonate-based polymer, a lithium acrylsulfonate-based polymer, and a lithium methylallylsulfonate-based polymer. It is selected from any one or a combination of at least two of the following: a polymer, a lithium 4-vinylbenzenesulfonate-based polymer, a lithium allylvinylsulfonate-based polymer, a lithium 3-sulfopropyl methacrylate-based polymer, a lithium 2-sulfoethyl methacrylate-based polymer, a lithium 2-acrylamido-2-methyl-1-propanesulfonate-based polymer, a lithium acrylate-2-acrylamido-2-methylpropanesulfonate-based polymer, and a lithium 3-allyloxy-2-hydroxy-1-propanesulfonate-based polymer.

[0014] Preferably, the metal bissulfonylimide-based polymer is selected from metal vinyl bissulfonylimide-based polymers and / or metal styrene bissulfonylimide-based polymers, and more preferably is lithium vinyl bissulfonylimide-based polymers and / or lithium styrene bissulfonylimide-based polymers.

[0015] In this application, the "polymer" in the polymer metal salt comprises homopolymers and / or copolymers, and, taking "metal methacrylate-based polymer" as an example, the polymer may be a homopolymer of metal methacrylate or a copolymer of metal methacrylate and other monomers, provided that it comprises structural units formed by metal methacrylate. Other polymers have the same meaning and are not described further for convenience.

[0016] Preferably, the weight-average molecular weight of the polymer metal salt is 1000 to 10000000, and may be, for example, 2000, 5000, 8000, 10000, 30000, 50000, 80000, 100000, 300000, 500000, 800000, 1000000, 3000000, 5000000, 7000000, or 9000000 and specific point values ​​between the above point values, and for the sake of the length and simplicity of the document, the present application does not further enumerate specific point values ​​included in the above range.

[0017] In the present application, the polymer metal salt can be obtained by purchasing it commercially or can be formed by metal chlorinating an acidic polymer through a method known in the prior art.

[0018] Preferably, based on 100% of the total mass of the polymer metal salt and the polymerizable monomer, the mass of the polymer metal salt is 1 to 90%, and may be, for example, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85% and specific point values ​​between the above point values, and for the sake of length and simplicity of the document, the present application does not further enumerate specific point values ​​included in the above range, and more preferably is 10 to 50%.

[0019] As a preferred technical solution of the present application, the mass ratio of the polymer metal salt is 1 to 90%, more preferably 10 to 50%, thereby allowing the copolymer formed by the reaction to contain a suitable proportion of polymer metal salt structural fragments, and allowing the aqueous adhesive to have excellent adhesive performance and lithium-ion conductivity while exhibiting appropriate swelling characteristics, so that the lithium-ion battery containing the aqueous adhesive has superior cycle performance and scaling performance. If the mass ratio of the polymer metal salt is too low, the strength of the aqueous adhesive decreases, and at the same time, the swelling rate in the electrolyte increases, causing the adhesive strength to deteriorate significantly after long-term use and resulting in insufficient cycle performance of the battery; if the mass ratio of the polymer metal salt is too high, the flexibility of the aqueous adhesive is insufficient, affecting the processing performance of the electrode piece.

[0020] Preferably, the acrylate monomer is an alkyl acrylate and / or an alkyl methacrylate.

[0021] Preferably, the "alkyl" in the alkyl acrylate and alkyl methacrylate is independently a C1-C10 straight-chain or branched-chain alkyl, for example, a C1, C2, C3, C4, C5, C6, C7, C8, C9, or C10 straight-chain or branched-chain alkyl; for example, when the alkyl is C1, i.e., methyl acrylate or methyl methacrylate; the rest can be inferred in the same way, but for simplicity, they are not explained again.

[0022] Preferably, the acrylate monomer comprises any one or a combination of at least two of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, pentyl acrylate, pentyl methacrylate, hexyl acrylate, hexyl methacrylate, octyl acrylate, isooctyl acrylate, or octyl methacrylate.

[0023] Preferably, the olefin monomer comprises any one or at least two combinations of styrene, C5 to C10 (e.g., C5, C6, C7, C8, C9, or C10) straight-chain or branched-chain olefins.

[0024] Preferably, the C5-C10 (e.g., C5, C6, C7, C8, C9, or C10) straight-chain or branched-chain olefins include, exemplarily, pentene, hexene, heptene, octene, nonene, decene, etc., and various isomers of the aforementioned olefins, but are not limited thereto.

[0025] Preferably, the mass ratio of the acrylate monomer and the olefin monomer is (0.5 to 2):1, and may be, for example, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1 or 1.9:1, and more preferably (0.8 to 1.5):1.

[0026] As a preferred technical solution of the present application, the mass ratio of the acrylate-based monomer and the olefin-based monomer is (0.5 to 2):1, and more preferably (0.8 to 1.5):1, which ensures that the copolymer formed by the reaction contains a specific ratio of polyacrylate structural fragments and polyolefin structural fragments, and that the aqueous adhesive possesses appropriate swelling characteristics, excellent adhesive performance, and lithium-ion conductivity; by controlling the ratio of two types of polymerizable monomers with different solubility parameters, products with different solubility parameters are obtained, and the swelling performance of the aqueous adhesive in the electrolyte can be controlled, so that neither loss of adhesive strength due to excessively high swelling nor loss of lithium-ion conductivity due to excessively low swelling occurs. If the amount of the acrylate-based monomer is too high, the swelling of the aqueous adhesive in the electrolyte increases, and the adhesive strength decreases after long-term use, resulting in insufficient cycle performance of the battery; If the capacity of the olefin monomer is too high, the swelling of the water-based adhesive is reduced, so the lithium-ion conductivity is not well exhibited, which affects the battery electrode and the scaling performance of the lithium-ion battery.

[0027] Preferably, the polymerizable monomer further comprises a functional monomer.

[0028] Preferably, the functional monomer comprises acrylic acid and / or methacrylic acid.

[0029] Preferably, the mass percentage of the functional monomer among the polymerizable monomers is ≤10%, and may be, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, or 9.5%, etc.

[0030] As a preferred technical solution of the present application, the polymerizable monomer further comprises a functional monomer to help improve the emulsion stability of the aqueous adhesive.

[0031] In a second aspect, embodiments of the present application provide a method for manufacturing an aqueous adhesive as described in the first aspect, said method comprising the step of mixing a polymer metal salt, a polymerizable monomer, an initiator, and a solvent, and then reacting them to obtain said aqueous adhesive.

[0032] Preferably, the initiator comprises a persulfate, more preferably ammonium persulfate.

[0033] Preferably, based on 100% of the mass of the polymerizable monomer, the mass of the initiator is 0.05 to 5%, and may be, for example, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or 4.5% and specific point values ​​between the above-mentioned point values; and for the sake of the length and simplicity of the document, the present application does not further enumerate specific point values ​​included in the above range.

[0034] Preferably, the solvent includes water.

[0035] Preferably, the reaction temperature is 60 to 80°C, and may be, for example, 61°C, 63°C, 65°C, 68°C, 70°C, 71°C, 73°C, 75°C, 77°C, or 79°C and specific point values ​​between the above-mentioned point values; and for the sake of the length and simplicity of the document, the present application does not further enumerate specific point values ​​included in the above range.

[0036] Preferably, the reaction time is 1 to 12 hours, and may be, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, or 11 hours and specific point values ​​between the above-mentioned point values, and for the sake of the length and simplicity of the document, the present application does not further enumerate specific point values ​​included in the above range.

[0037] Preferably, the above reaction further includes a neutralization step after completion.

[0038] Preferably, the neutralizing reagent is a lithium hydroxide solution.

[0039] In a third aspect, an embodiment of the present application provides an application of an aqueous adhesive in a battery material as described in the first aspect.

[0040] Preferably, the battery material is a lithium-ion battery material.

[0041] In a fourth aspect, an embodiment of the present application provides a battery electrode, said battery electrode comprising an aqueous adhesive as described in the first aspect.

[0042] Preferably, the battery electrode comprises a current collector and a coating layer installed on the current collector, and the material of the coating layer comprises an aqueous adhesive as described in the first side.

[0043] Preferably, the material of the coating layer comprises an active material, a conductive agent, and an aqueous adhesive as described in the first aspect.

[0044] Preferably, the battery electrode is a negative electrode.

[0045] In a fifth aspect, an embodiment of the present application provides a lithium-ion battery, said lithium-ion battery comprising at least one of an aqueous adhesive as described in the first aspect and a battery electrode as described in the fourth aspect.

[0046] Compared to related technologies, the embodiments of the present application have the following beneficial effects:

[0047] In the aqueous adhesive provided in the embodiment of the present application, through the design of structural units such as polymer metal salts and polymerizable monomers and their mutual cooperation, the formed copolymer segment is configured to include specific repeating structural units, and the aqueous adhesive is configured to have appropriate swelling characteristics, excellent adhesive performance, and lithium-ion conductivity, and its swelling rate in the electrolyte (85°C, 24 hours) is adjustable within the range of 10 to 100%, and the peel stress is 15 to 30 N / m, and it combines excellent adhesive strength, adhesive stability, and electrochemical properties, thereby significantly improving the cycle performance and scaling performance of a lithium-ion battery containing the same. The aqueous adhesive is used in a negative electrode plate, and the capacity retention rate of the lithium-ion battery after 100 cycles at room temperature is ≥98%, and the 3C capacity retention rate is ≥94%, and since the cycle performance and scaling performance are excellent, it can satisfy the application requirements of a high-performance lithium-ion battery.

[0048] After reading and understanding the drawings and detailed descriptions, you can understand other aspects. Specific details for implementing the invention

[0049] The technical solution of the present application is further explained below through specific embodiments. Those skilled in the art should understand that the above embodiments are merely for the purpose of aiding understanding of the present application and should not be construed as specific limitations on the present application.

[0050] As used herein, the terms “include,” “comprehensively,” “comprise,” “contain,” or any other variation thereof are intended to cover non-exclusive inclusion. For example, a composition, step, method, product, or device comprising the listed elements is not limited to these elements and may include other elements not explicitly listed or elements inherent to such composition, step, method, product, or device.

[0051] "Optional" or "any one" indicates that the matter or event described below may or may not occur, and this description includes situations in which the event occurs and situations in which the event does not occur.

[0052] In this application, the indefinite determiners "one" and "one" preceding an element or component do not limit the quantity requirement (i.e., the number of times it appears) of the element or component. Accordingly, "one" or "one" should be interpreted as including one or at least one, and unless it is evident that the number refers only to the singular form, the singular element or component also includes the plural form.

[0053] Descriptions of terms such as “one embodiment,” “some embodiment,” “exemplary,” “specific example,” or “some example” as used in this application indicate that the specific features, structures, materials, or properties described in combination with these embodiments or examples are included in at least one embodiment or example of this application. As used herein, general expressions of the above terms do not necessarily refer to the same embodiment or example.

[0054] In addition, the technical features of each embodiment of the present application may be combined with one another as long as they do not conflict with one another.

[0055] Example 1

[0056] In the aqueous adhesive and the method for manufacturing the same, the aqueous adhesive is a copolymer formed by the reaction of lithium polyacrylate (weight average molecular weight of 10,000, purchased from McClean) and a polymerizable monomer, and the mass ratio of lithium polyacrylate to the polymerizable monomer is 1:2; the polymerizable monomer is a mixed monomer of styrene (St), butyl acrylate (BA), and acrylic acid (AA), and comprises 50% styrene, 48% butyl acrylate, and 2% acrylic acid based on mass percentage.

[0057] The method for manufacturing the above aqueous adhesive is as follows: 50 parts by mass of lithium polyacrylate is added to 550 parts by mass of deionized water and heated to 70°C and stirred, then 100 parts by mass of a polymerizable monomer (a mixed monomer as described above) is added, and 0.25 parts by mass of ammonium persulfate is added and reacted for 6 hours, and after the reaction is completed, the pH is adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above aqueous adhesive.

[0058] Example 2

[0059] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that lithium polyacrylate is replaced with an equal mass of poly 2-methyl-2-acrylate-2-hydroxyethyl potassium phosphate (weight-average molecular weight is 10,000, purchased from McClean), and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0060] Example 3

[0061] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that lithium polyacrylate is replaced with an equal mass of sodium polystyrene sulfonate (weight-average molecular weight is 10,000 and is purchased from McClean), and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0062] Example 4

[0063] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that lithium polyacrylate is replaced with an equal mass of lithium poly(vinyl bissulfonylimide) (weight-average molecular weight is 10,000 and is purchased from McClean), and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0064] Example 5

[0065] In the aqueous adhesive and the method for manufacturing the same, the only difference from Example 1 is that the mass ratio of lithium polyacrylate to polymerizable monomer is 1:49, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0066] Example 6

[0067] In the aqueous adhesive and the method for manufacturing the same, the only difference from Example 1 is that the mass ratio of lithium polyacrylate to polymerizable monomer is 4:1, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0068] Example 7

[0069] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that the molecular weight of the lithium polyacrylate is 100,000, and all other components, ratios, and manufacturing methods are the same as those in Example 1.

[0070] Example 8

[0071] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that the molecular weight of the lithium polyacrylate is 1,000,000, and all other components, ratios, and manufacturing methods are the same as those in Example 1.

[0072] Example 9

[0073] In the aqueous adhesive and the method for manufacturing the same, the difference from Example 1 is that the mass ratio of lithium polyacrylate to the polymerizable monomer is 1:1; the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, and contains 40% styrene, 52% butyl acrylate, and 8% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0074] Example 10

[0075] In the aqueous adhesive and the method for manufacturing the same, the difference from Example 1 is that the mass ratio of lithium polyacrylate to the polymerizable monomer is 1:9; the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, and contains 52% styrene, 43% butyl acrylate, and 5% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0076] Example 11

[0077] In the aqueous adhesive and the method of manufacturing the same, the difference from Example 1 is that the polymerizable monomer comprises 35% styrene, 60% butyl acrylate, and 5% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0078] Example 12

[0079] In the aqueous adhesive and the method of manufacturing the same, the difference from Example 1 is that the polymerizable monomer comprises 60% styrene, 35% butyl acrylate, and 5% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0080] Comparative Example 1

[0081] In the aqueous adhesive and the method for manufacturing the same, the aqueous adhesive is a copolymer of polymerizable monomers (styrene, butyl acrylate and acrylic acid), and the polymerizable monomer comprises 50% styrene, 48% butyl acrylate and 2% acrylic acid based on mass percentage.

[0082] The method for manufacturing the above aqueous adhesive is as follows: 50 parts by mass of a polymerizable monomer is added to 200 parts by mass of deionized water, and 0.25 parts by mass of ammonium persulfate is added and reacted at 70°C for 6 hours. After the reaction is completed, the pH is adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above aqueous adhesive.

[0083] Comparative Example 2

[0084] In the aqueous adhesive and the method of manufacturing the same, the only difference from Example 1 is that the polymerizable monomer is a mixed monomer of styrene and acrylic acid, containing 98% styrene and 2% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0085] Comparative Example 3

[0086] In the aqueous adhesive and the method of manufacturing the same, the difference from Example 1 is that the polymerizable monomer is a mixed monomer of butyl acrylate and acrylic acid, and contains 98% butyl acrylate and 2% acrylic acid based on mass percentage, and all other components, ratios, and manufacturing methods are the same as in Example 1.

[0087] Comparative Example 4

[0088] In a water-based adhesive and a method for manufacturing the same, the water-based adhesive is a copolymer formed by the reaction of lithium acrylate (LiAA) and a polymerizable monomer, and the mass ratio of lithium acrylate to the polymerizable monomer is 1:2; the polymerizable monomer is a mixed monomer of styrene, butyl acrylate, and acrylic acid, and comprises 50% styrene, 48% butyl acrylate, and 2% acrylic acid based on mass percentage.

[0089] The method for manufacturing the above aqueous adhesive is as follows: 50 parts by mass of lithium acrylate and 100 parts by mass of polymerizable monomer are added to 550 parts by mass of deionized water, and 0.75 parts by mass of ammonium persulfate are added and reacted at 70°C for 6 hours. After the reaction is completed, the pH is adjusted to 7.0 with a 10% lithium hydroxide solution to obtain the above aqueous adhesive.

[0090] Comparative Example 5

[0091] In the aqueous adhesive and the method for manufacturing the same, the aqueous adhesive is a mixture of lithium polyacrylate and a ternary copolymer of styrene-butyl acrylate-acrylic acid, and the mass ratio of lithium polyacrylate to the ternary copolymer is 1:2; and the polymerization monomer of the ternary copolymer comprises 50% styrene, 48% butyl acrylate, and 2% acrylic acid based on mass percentage.

[0092] The method for manufacturing the above aqueous adhesive is as follows: 100 parts by mass of a polymerization monomer of a ternary copolymer is added to 500 parts by mass of deionized water, and 0.25 parts by mass of ammonium persulfate is added and reacted at 70°C for 6 hours; after the reaction is completed, the pH is adjusted to 7.0 with a 10% lithium hydroxide solution; then, 50 parts by mass of lithium polyacrylate is added to the system, stirred at room temperature, and uniformly mixed to obtain the above aqueous adhesive.

[0093] Comparative Example 6

[0094] It is a commercially available water-based adhesive, an SBR adhesive.

[0095] Comparative Example 7

[0096] LA132 is a commercially available water-based adhesive.

[0097] Application example

[0098] A battery electrode comprising a current collector (Cu foil) and a coating layer installed on the current collector, wherein the material of the coating layer comprises a negative electrode active material (silicon oxide material SiO-450, BTR New Material Group Co., Ltd., silicon content 10%), a conductive agent (carbon black SP), an adhesive, and a thickener (sodium carboxymethylcellulose, CMC), and the adhesive is an aqueous adhesive provided in Examples 1 to 12 and Comparative Examples 1 to 7, respectively.

[0099] The method for manufacturing the above-mentioned cathode electrode is as follows: a cathode active material, a conductive agent, an adhesive, and a thickener are mixed in a mass ratio of 96.5:1.0:1.0:1.5, and added to deionized water at a ratio where the system solid content is 40 wt%, and thoroughly stirred and mixed to prepare a uniform cathode slurry; after passing through a 100-mesh sieve, the mixture is coated onto a Cu foil serving as a cathode current collector, dried, and then processed using a roller to form a 10×10 per unit length 4 A negative electrode piece was obtained by rolling with a load of N / m.

[0100] A lithium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the aforementioned negative electrode, and the manufacturing method is as follows:

[0101] (1) Manufacture of a positive electrode: A positive active material (lithium iron phosphate material), conductive carbon black, and adhesive (PVDF) are mixed in a mass ratio of 96.5:2.0:2.5 based on solid content, respectively, and according to the ratio where the system solid content is 50 wt% N - Methylpyrrolidone (NMP) is added and thoroughly stirred and mixed to prepare a uniform anode slurry; after passing it through a 100-mesh sieve, it is coated onto an Al foil serving as the anode current collector, dried, and then processed using a roller to form 10×10 per unit length 4 Obtaining a positive electrode piece by rolling with an applied load of N / m;

[0102] (2) Cathode electrode: As described above;

[0103] (3) Separator: PE porous polymer film (Shenzhen Senior Technology Material Co., Ltd.) was adopted as the separator;

[0104] (4) Assembly of a lithium-ion battery: A battery cell is obtained by sequentially winding a positive electrode, a separator, and a negative electrode; the battery cell is sealed in an aluminum plastic film, moisture is removed through baking, an electrolyte is injected, and the lithium-ion battery is obtained through processes such as vacuum sealing, storage, formation, double sealing, and molding.

[0105] Performance Test:

[0106] (1) Swelling performance

[0107] A water-based adhesive to be tested was added to a clean mold by a drop method to ensure a solid content of 4g ± 0.1g, then dried in an oven at 70°C for 12 hours, removed, cut into pieces of 1cm × 1cm, dried at 120°C for 2 hours, and prepared for later use; the well-prepared film piece was weighed and recorded as mass M1; about 5g of electrolyte was weighed and added to a glass bottle containing the aforementioned film piece to ensure the film piece was completely submerged in the electrolyte, the bottle was sealed, and left in a water bath at 85°C for 24 hours. The film piece was removed from the glass bottle, the electrolyte on the film piece was wiped off with clean, dust-free paper, and the mass of the swollen film piece was weighed and recorded as M2.

[0108] Swelling rate = 100% × (M2 - M1) / M1.

[0109] (2) Adhesion performance

[0110] A cathode piece is cut into a long strip shape of 20 cm × 2.5 cm and bonded to a steel plate with a thickness of 1 mm using double-sided tape on the current collector side, and a transparent tape is attached to the coating layer side. The coating layer is peeled in a 180° direction at a speed of 100 mm / min using a tensile testing machine, and the peeling stress is measured. This peeling stress is considered as a criterion for judging adhesive performance, and a higher peeling stress indicates better adhesive strength.

[0111] (3) Battery cycle performance and scaling performance

[0112] Initial adjustment was performed by charging the above-described manufactured lithium-ion battery to 4.2V with a constant current of 0.33C, then charging with a constant voltage until the cutoff current becomes 0.02C, and discharging to 2.5V with 0.33C; leaving it for 5 minutes, then charging to 4.2V with a constant current of 0.33C, then charging with a constant voltage until the cutoff current becomes 0.02C, and discharging to 2.5V with 0.33C;

[0113] A lithium-ion battery initially regulated at 25°C was charged to 4.2V with a constant current of 0.5C, then charged at a constant voltage until the cutoff current reached 0.02C and left for 5 minutes, after which it was discharged to 2.5V with a constant current of 1C and left for 5 minutes to measure the initial cycle discharge capacity. This process was repeated, and after 100 charge / discharge cycles, the 100th cycle discharge capacity was measured; the 100th cycle capacity retention rate was then calculated using the following formula:

[0114] Capacity retention rate (%) after 100 cycles = 100% × 100th cycle discharge capacity / First cycle discharge capacity.

[0115] Scaling performance: A lithium-ion battery initially regulated at 25°C was charged to 4.2V with a constant current of 0.5C, then charged at a constant voltage until the cutoff current was 0.02C, left for 5 minutes, then discharged to 2.5V with a constant current of 1C, and left for 5 minutes to measure the 1C discharge capacity. Then, it was charged to 4.2V with a constant current of 0.5C, then charged at a constant voltage until the cutoff current was 0.02C, left for 5 minutes, then discharged to 2.5V with a constant current of 3C, and left for 5 minutes to measure the discharge capacity at a 3C scaling.

[0116] 3C capacity retention rate (%) = 100% × 3C discharge capacity / 1C discharge capacity.

[0117] The results of the performance tests are as shown in Tables 1 and 2.

[0118] Table 1

[0119]

[0120] In Table 1, "--" indicates that this component is not included and this data does not exist.

[0121] Table 2

[0122]

[0123] When combining the performance test data of Table 1 and Table 2, compared to commercially available SBR aqueous adhesive (Comparative Example 6) and LA132 adhesive (Comparative Example 7), the present application, through the design of structural units of polymer metal salts and polymerizable monomers and their mutual cooperation, has an aqueous adhesive with appropriate swelling characteristics, and the swelling rate after being left in an electrolyte at 85°C for 24 hours can be adjusted within the range of 10 to 100%, and has excellent adhesive performance and lithium-ion conductivity, and the peeling stress for the negative electrode is 15 to 30 N / m, and the adhesive strength is significantly improved compared to commercially available aqueous adhesives, and also has excellent lithium-ion conductivity, scaling performance, and cycle performance, and a lithium-ion battery containing it has a capacity retention rate of 97.5 to 99% after 100 cycles at room temperature and a 3C capacity retention rate of 94 to 96.3%, and it can be seen that the cycle performance and scaling performance are significantly improved. At the same time, by adjusting the ratio of polymer metal salts to polymerizable monomers and designing the ratio of acrylate-based monomers to olefin-based monomers among the polymerizable monomers, it is possible to adjust and optimize the performance of water-based adhesives.

[0124] The aqueous adhesive provided in this application is a copolymer formed by the reaction of a polymeric metal salt and a polymerizable monomer, wherein the polymerizable monomer includes acrylate-based monomers and olefin-based monomers. Through the design of structural units within the copolymer, the aqueous adhesive achieves an excellent balance effect between adhesive performance, lithium-ion conductivity, and swelling characteristics, so that the adhesive does not suffer from loss of adhesive strength due to excessively high swelling, nor does it suffer from loss of lithium-ion conductivity due to excessively low swelling, and possesses excellent adhesive strength, adhesive stability, and electrochemical properties. If the aqueous adhesive does not include structural units of the polymeric metal salt (Comparative Example 1), its swelling rate in the electrolyte is too high and its adhesive strength and lithium-ion conductivity are insufficient, severely degrading the cycle performance and scaling performance of the battery; if the polymerizable monomer does not include an acrylate-based monomer (Comparative Example 2), the adhesive performance of the aqueous adhesive is poor and the cycle and scaling performance of the battery are reduced; When the polymerizable monomer does not include an olefin-based monomer (Comparative Example 3), the performance of the aqueous adhesive deteriorates, resulting in a decrease in the capacity retention rate of the lithium-ion battery and poor cycle performance. Additionally, when a polymer metal salt and a styrene-butyl acrylate-acrylic acid ternary copolymer are present in the adhesive in a blended form (Comparative Example 5), or when a metal salt containing a double bond is copolymerized with another polymerizable monomer (Comparative Example 4), it is not possible to form a copolymer containing specific repeating units and segment structures, which lowers the adhesive strength of the aqueous adhesive and reduces battery cycle performance.

[0125] The applicant declares that while this application describes the aqueous adhesive, its manufacturing method, and its applications through the embodiments described above, this application is not limited to the embodiments described above, meaning that this application does not imply that it can be practiced by relying on the embodiments described above. Those skilled in the art should understand that all improvements to this application, equivalent substitutions for each raw material of the product of this application, addition of auxiliary components, and selection of specific methods are all within the scope of protection and disclosure of this application.

Claims

Claim 1 A water-based adhesive, wherein the water-based adhesive is a copolymer formed by a polymer metal salt and a polymerizable monomer; wherein the polymerizable monomer comprises a combination of an acrylate monomer and an olefin monomer; wherein the mass ratio of the acrylate monomer and the olefin monomer is (0.5 to 2):1, and the olefin monomer comprises any one or at least two combinations of styrene, C5 to C10 straight-chain or branched-chain olefins; and wherein the polymer metal salt is selected from any one or at least two combinations of a metal phosphate polymer, a metal carboxylate polymer, a metal sulfonate polymer, or a metal bissulfonylimide polymer. Claim 2 An aqueous adhesive according to claim 1, wherein the polymer metal salt comprises any one or a combination of at least two of a polymer lithium salt, a polymer sodium salt, a polymer potassium salt, or a polymer magnesium salt. Claim 3 An aqueous adhesive according to claim 1 or 2, wherein the metal phosphate-based polymer is selected from any one or a combination of at least two of metal polyphosphate, metal 2-methyl-2-acrylate-2-hydroxyethyl phosphate-based polymer, metal bis(2-(methacryloyloxy)ethyl)phosphate-based polymer, metal 2-methacryloyloxyethyl phosphate-based polymer, or metal vinyl phosphate-based polymer. Claim 4 An aqueous adhesive according to claim 1 or 2, wherein the metal carboxylate-based polymer is selected from any one or a combination of at least two of metal methacrylate-based polymers, metal acrylate-based polymers, metal maleate-based polymers, metal itaconate-based polymers, metal trialyl citrate-based polymers, metal carboxymethylcellulose-based polymers, or metal alginate-based polymers. Claim 5 An aqueous adhesive according to claim 1 or 2, wherein the metal sulfonate-based polymer is selected from any one or a combination of at least two of a metal styrene sulfonate-based polymer, a metal vinyl sulfonate-based polymer, a metal acrylsulfonate-based polymer, a metal methylallyl sulfonate-based polymer, a metal 4-vinylbenzene sulfonate-based polymer, a metal allylvinyl sulfonate-based polymer, a metal 3-sulfopropyl methacrylate-based polymer, a metal 2-sulfoethyl methacrylate-based polymer, a metal 2-acrylamido-2-methyl-1-propanesulfonate-based polymer, a metal acrylate-2-acrylamido-2-methylpropanesulfonate-based polymer, and a metal 3-allyloxy-2-hydroxy-1-propanesulfonate-based polymer. Claim 6 An aqueous adhesive according to claim 1 or 2, wherein the metal bissulfonylimide-based polymer is selected from metal vinyl bissulfonylimide-based polymer and / or metal styrene bissulfonylimide-based polymer. Claim 7 An aqueous adhesive according to claim 1 or 2, wherein the weight-average molecular weight of the polymer metal salt is 1,000 to 1,000,000. Claim 8 An aqueous adhesive according to claim 1 or 2, wherein the mass of the polymer metal salt is 1 to 90% based on 100% of the total mass of the polymer metal salt and the polymerizable monomer. Claim 9 An aqueous adhesive according to claim 1 or 2, wherein the mass of the polymer metal salt is 10 to 50% based on 100% of the total mass of the polymer metal salt and the polymerizable monomer. Claim 10 An aqueous adhesive according to claim 1 or 2, wherein the acrylate-based monomer is an alkyl acrylate and / or alkyl methacrylate. Claim 11 An aqueous adhesive according to claim 1 or 2, wherein the acrylate-based monomer comprises any one or a combination of at least two of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, pentyl acrylate, pentyl methacrylate, hexyl acrylate, hexyl methacrylate, octyl acrylate, isooctyl acrylate, or octyl methacrylate. Claim 12 A water-based adhesive according to claim 1 or 2, wherein the mass ratio of the acrylate-based monomer to the olefin-based monomer is (0.8 to 1.5):

1. Claim 13 An aqueous adhesive according to claim 1 or 2, wherein the polymerizable monomer further comprises a functional monomer, wherein the functional monomer comprises acrylic acid and / or methacrylic acid. Claim 14 An aqueous adhesive according to claim 13, wherein the mass percentage of the functional monomer among the polymerizable monomers is ≤10%. Claim 15 A method for manufacturing an aqueous adhesive according to claim 1 or 2, comprising the step of mixing a polymer metal salt, a polymerizable monomer, an initiator, and a solvent, and then reacting them to obtain the aqueous adhesive. Claim 16 In claim 15, the manufacturing method comprises an initiator comprising ammonium persulfate. Claim 17 A method of manufacturing according to claim 15, wherein the mass of the initiator is 0.05 to 5% based on 100% of the mass of the polymerizable monomer. Claim 18 A method of manufacturing according to claim 15, wherein the solvent comprises water, the reaction temperature is 60 to 80°C, and the reaction time is 1 to 12 hours. Claim 19 A manufacturing method according to claim 15, wherein the above reaction further includes a neutralization step after completion. Claim 20 A battery material comprising an aqueous adhesive according to paragraph 1 or 2. Claim 21 A battery electrode comprising an aqueous adhesive according to paragraph 1 or 2. Claim 22 In claim 21, the battery electrode comprises a current collector and a coating layer installed on the current collector, wherein the material of the coating layer comprises the aqueous adhesive. Claim 23 In Clause 21, the battery electrode is a negative electrode. Claim 24 A lithium-ion battery comprising an aqueous adhesive according to paragraph 1 or 2.

Citation Information

Patent Citations

  • Preparation method of negative pole piece water-based binder

    CN111057184A

  • Binder for non-aqueous electrolye rechargeable battery, negative electrode slurry for rechargeable battery including the same, negative electrode for rechargeable battery including the same and rechargeable battery including the same

    KR1020200125503A